Yinzhihuang oral liquid combined with phototherapy for neonatal jaundice: a systematic review and meta-analysis of randomized clinical trials - Ruo-han Wu; Shuo Feng; Mei Han; Patrina Caldwell; Shi-gang Liu; Jing Zhang; Jian-ping Liu (BMC, 2018)
Abstract Background Neonatal jaundice affects at least 481,000 newborns every year. Phototherapy is recommended but it's effects are limited and adverse reactions can occur. In China, phototherapy combined with Yinzhihuang oral liquid is also used for this condition. This systematic review evaluated the effectiveness and safety of combination therapy with Yinzhihuang oral liquid and phototherapy compared to phototherapy alone for treating neonatal jaundice. Method A comprehensive literature search was performed in four Chinese databases, two English language databases and two trial registries from inception to June 2017. Two authors independently screened the citations and retrieved full publications for randomized trials on Yinzhihuang oral liquid combined with phototherapy for neonatal jaundice. The methodological quality of the trials was assessed according to the Cochrane Collaboration's tool for assessing risk of bias. Data were analyzed using RevMan 5.3. Result Totally 17 trials (involving 2561 neonates) were included in this review. Fourteen of them had a high risk of bias. Significant differences were detected between combination therapy and phototherapy alone for serum bilirubin level (MD − 50.25 μmol/L, 95% CI -64.01 to − 36.50, I2 = 98%; 7 trials, post-hoc decision choosing random effects model), failure of jaundice resolution (RR 0.21, 95% CI 0.14 to 0.32, I2 = 0%; 11 trials, fixed effects model), and time to jaundice resolution (MD − 2.17 days, 95%CI -2.96 to − 1.38, I2 = 98%; 6 trials, random effects model). Adverse events were reported in eight trials but none were serious. Trial sequential analysis for serum bilirubin level suggested that the cumulative Z-curve (which represents 1478 participants) reached the required information size (DARIS = 1301 participants). Conclusion Based on trials with low methodological quality, Yinzhihuang oral liquid combined with phototherapy seemed to be safe and superior to phototherapy alone for reducing serum bilirubin in neonatal jaundice. These potential benefits need to be confirmed in future trials using rigorous methodology. Trial registration Systematic review registration: [PROSPERO registration: CRD42016037691].